Star-planet interactions: I. Stellar rotation and planetary orbits - VIDOTTO, ALINE (My University, 2016)
Context. As a star evolves, planet orbits change over time owing to tidal interactions, stellar mass losses, friction and gravitational drag forces, mass accretion, and evaporation on/by the planet. Stellar rotation modifies the structure of the star and therefore the way these different processes occur. Changes in orbits, subsequently, have an impact on the rotation of the star. Aims. Models that account in a consistent way for these interactions between the orbital evolution of the planet and the evolution of the rotation of the star are still missing. The present work is a first attempt to fill this gap. Methods. We compute the evolution of stellar models including a comprehensive treatment of rotational effects, together with the evolution of planetary orbits, so that the exchanges of angular momentum between the star and the planetary orbit are treated in a self-consistent way. The evolution of the rotation of the star accounts for the angular momentum exchange with the planet and also follows the effects of the internal transport of angular momentum and chemicals. These rotating models are computed for initial masses of the host star between 1.5 and 2.5 M⊙, with initial surface angular velocities equal to 10 and 50% of the critical velocity on the zero age main sequence (ZAMS), for a metallicity Z = 0.02, with and without tidal interactions with a planet. We consider planets with masses between 1 and 15 Jupiter masses (MJ), which are beginning their evolution at various distances between 0.35 and 4.5 au. Results. We demonstrate that rotating stellar models without tidal interactions and without any wind magnetic braking during the red giant phase can well reproduce the surface rotations of the bulk of red giants. However, models without any interactions cannot account for fast rotating red giants in the upper part of the red giant branch, where these models, whatever the initial rotation considered on the ZAMS, always predict very low velocities. For these stars, some interaction with a companion is highly probable and the present rotating stellar models with planets confirm that tidal interaction can reproduce their high surface velocities. We also show that the minimum distance between the planet and the star on the ZAMS, which enables the planet to avoid engulfment and survive (i.e. the survival limit) is decreased around faster rotating stars.
PUBLISHED
Cited By :3 Export Date: 26 January 2017
Keywords: stars: evolution / stars: rotation / planetary systems; stars: evolution / stars: rotation / planetary systems